Comparison effects of nano-magnesium oxide and advanced platelet rich fibrin on the healing of tenotomized Achilles tendon in dogs - Al-qadhi, Ahmed; Thanoon, Moyaser; Al-Ajeli, Radhwan; Zedan, Ibraheem Ahmed; Mohammed, Fouad (Iraqi journal of veterinary sciences, 2026)
The study aims to compare effects of local application of liquid magnesium oxide nanoparticles (MgO-NPs) and advanced platelet rich fibrin (A-PRF) on healing of the severed superficial digital flexor tendon in dogs (SDFT). The study was conducted on Twenty-seven mature dogs. Their weights ranged between 25-30 kg. while their ages ranged from 18-24 months. The dogs were randomly divided in three groups equally. The first (control group) in which the complete cutting SDFT was sutured without the addition of any adjuvant. In the second group there was a suture of cutting SDFT with the addition of 3ml of Nano-magnesium oxide. In the third group there was a suture of cutting SDFT with the addition of 3ml of advanced platelet rich fibrin. In one group, animals were divided into three subgroups equally that were examined after 15, 30, 45 days of surgery. Evaluated the severity of lameness, adhesion, histopathological and immunohistochemical examination of the healed tendons were performed after 15,30,45 days of surgery in each group. in comparison to the control, the adhesion degree more than A-PRF and MgO-NPs. The results of histopathological examination of SDFT healing in first group reveled sever infiltration of mononuclear inflammatory cell, proliferation of tenocyte deposition of collagen bundle without orientation and angled toward axis of tendon and newly capillary while in second and third groups the result show slightly to moderate respectively. The result of immunohistochemical examination in the first group showed moderate positive collagen reaction, in second group with intense positive collagen reaction, while in third group very slight positive collagen reaction in all periods except in 45 days the third group show intense positive collagen reaction. Therefore, it could be concluded that the MgO-NPs and A-PRF are effective materials for enhancing SDFT healing in dogs but the MgO-NPs group better than the A-PRF group.